2020
DOI: 10.3390/sym12010077
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Criteria Group Decision-Making for Selection of Green Suppliers under Bipolar Fuzzy PROMETHEE Process

Abstract: The preference ranking organization method for enrichment of evaluations (PROMETHEE) method considers a significant outranking class of multi-criteria decision analysis (MCDA), as it is easy to deal with its simple computations. In the PROMETHEE, different preference functions are used according to the type and nature of attributes or criteria that demonstrate the clearness and reliability of this method. This study provides a new version of the PROMETHEE method using bipolar fuzzy information, named the bipol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Akram and Arshad [2] initiated BF linguistic variables and BF numbers as a generalization of BFSs. The notion of BFSs has widely been applied in medical diagnosis, bipolar disorder, decision making, optimization, and others [3,4,40,77,78,105,15].…”
Section: Bipolar Complex Fuzzy Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Akram and Arshad [2] initiated BF linguistic variables and BF numbers as a generalization of BFSs. The notion of BFSs has widely been applied in medical diagnosis, bipolar disorder, decision making, optimization, and others [3,4,40,77,78,105,15].…”
Section: Bipolar Complex Fuzzy Setsmentioning
confidence: 99%
“…2. Next, to illustrate the strengths of the developed approaches, we also apply the existing methods [3,7,16,30,35,59] to the same numerical example discussed earlier. The results are summarized in Table 13.…”
Section: Comparative Studymentioning
confidence: 99%
“…For instance, Zhang et al [49] proposed an integrated group support with rough set theory and intuitionistic fuzzy sets by employing PROMETHEE II, thus claiming its effectiveness. Akram et al [50] suggested a multicriteria GDM model for selecting green suppliers under bipolar fuzzy PROMETHEE I and II, in which the performance ratings of three DMs are averaged for the group's ratings. On the other hand, Soba et al [51] made use of grey relation and PROMETHEE for the location selection of staffs in Turkey.…”
Section: Group Prometheementioning
confidence: 99%
“…Govindan et al [46] presented a compromise recommendation from an analysis of pairwise relations in the individuals' ranks. Akram et al [50] offered a bipolar fuzzy group PROMETHEE in which individuals' ratings are averaged into a group rating without thinking about a consensus. We observe that many interesting consensus reaching techniques can facilitate a compromise or an agreement for group PROMETHEE under the framework of Zhang et al [12], and these could be left for future study.…”
Section: Consensus Reachingmentioning
confidence: 99%
“…19 Some scholars demonstrated bipolar fuzzy aggregation operators [20][21][22] to enrich the mathematical calculation of bipolar fuzzy. Akram et al 23 took advantage of bipolar fuzzy and Preference Ranking Organization METHod for Enrichment of Evaluation (PROMETHEE) method resolving the problem of green supplier selection. Akram et al 24 combined bipolar fuzzy with TOPSIS method and ELimination Et Choice Translating REality (ELECTRE-I) method, respectively, to structure the MADM model.…”
mentioning
confidence: 99%